PENGEMBANGAN LABORATORIUM VIRTUAL PADA MATERI LAJU REAKSI UNTUK KIMIA DASAR II PRODI PENDIDIKAN KIMIA - Epinur Epinur (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
Reaction rate learning requires experiments or practicum identical to the laboratory, so the implementation of the lab is highly dependent on the existence and completeness of the laboratory. Chemical concepts based on experiments, one of which is the concept of reaction rate consisting of the concept of reaction rate, factors influencing rate and reaction order. With the advancement of technology in the field of ICT, there are many programs that can be utilized to design lab work based on ICT (virtual lab). Virtual labs can resolves the limitations of laboratories, tools and materials, time and cost savings. This development research aims to find out the process of developing a virtual laboratory on reaction rate material using Adobe Flash6 Professional program until it is declared eligible to be used for Basic Chemistry II course in chemical education program. This type of research is development research. The product developed in the form of virtual laboratory using Adobe Flash6 Professional program on reaction rate material for Chemistry II course in chemistry education program. The study of virtual laboratory development on this reaction rate material using the ADDIE model. Based on material and media validation, the resulting virtual lab is feasible and heavily used in learning. Keywords: Virtual lab, Adobe Flash CS6 Professional, Reaction rate